Investigating the factors influencing consumer trust in electronic commerce - Muhammad Rabiul Hasan (Kulliyyah of Information and Communication Technology,International Islamic University Malaysia, 2012)
Purchasing online is no more considered as new issue since 1990s. With the rapid growth of Information and Communication Technology (ICT), internet became a common platform for users to accomplish many tasks in a convenience way. Purchasing goods and services online is one of those activities that we accomplish over the internet. However, with the popularity of internet, still many online users (perceived consumers) do not purchase things online. Based on the existing literature, one of the main reasons found is the lack of consumer trust in online vendors. Therefore, this study focused on investigating the factors influencing consumer trust in e-commerce environment. The main objective of this research was to examine whether the perceived factors are influential towards consumer trust in e-commerce. The study involved a quantitative method for data collection and analysis. Out of 300 sets of questionnaire, 253 were useful for analysis and interpretation. The findings revealed that all the factors have positive and significant relationship to consumer trust in e-commerce. Discussions involved 360° view on the influential factors and their significance in e-commerce environment. Finally, future implications indicate a need of further study to understand wide range of perceived factors that could contribute towards the growth of participation in online purchasing.